STRUCTURAL SYNTACTIC ANALYSIS OF NOUN PHRASES IN INDONESIAN - Sitinjak, Vivi Novalia; Surbakti, Arya Alfines; Kristin, Nelly; Damanik, Andrini Aurellia Anggi; Sitohang, Arta Jelita (BASIS (Bahasa dan Sastra Inggris), 2023)
Syntax is a part of linguistics that studies how words are combined into sentences and phrases. In this study, we focus on analyzing the syntax of noun phrases in Indonesian. We use the treebank analysis technique to identify the syntactic structure of noun phrases in Indonesian. Study results show that noun phrases in Indonesian have complex and varied syntactic structures and that the context and types of noun phrases play an important role in influencing the syntactic structure of noun phrases. These findings are important for understanding how noun phrases are formed and understood in Indonesian and how it affects language processing.